2019
DOI: 10.3390/md17120654
|View full text |Cite
|
Sign up to set email alerts
|

Marine Polysaccharides in Pharmaceutical Applications: Fucoidan and Chitosan as Key Players in the Drug Delivery Match Field

Abstract: The use of marine-origin polysaccharides has increased in recent research because they are abundant, cheap, biocompatible, and biodegradable. These features motivate their application in nanotechnology as drug delivery systems; in tissue engineering, cancer therapy, or wound dressing; in biosensors; and even water treatment. Given the physicochemical and bioactive properties of fucoidan and chitosan, a wide range of nanostructures has been developed with these polysaccharides per se and in combination. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 149 publications
1
47
0
2
Order By: Relevance
“…These molecules can produce a spontaneous self-assembly or complexation with therapeutic agents. Polysaccharides such as chitosan, alginate, and pectin are among a few of the studied nanocarriers capable of forming self-assemblies with a wide range of molecules and therapeutic agents [12,13]. Pectin is a highly suitable molecule for drug delivery applications [14][15][16][17] due to its superior water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules can produce a spontaneous self-assembly or complexation with therapeutic agents. Polysaccharides such as chitosan, alginate, and pectin are among a few of the studied nanocarriers capable of forming self-assemblies with a wide range of molecules and therapeutic agents [12,13]. Pectin is a highly suitable molecule for drug delivery applications [14][15][16][17] due to its superior water solubility.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used as a drug carrier, especially for anti-cancer treatments and anti-biotics. Additionally, fucoidans have been shown to improve drug bioavailability and efficacy in pharmaceutical formulations, including in nanoparticles, liposomes, microparticles, and semisolid formulations [28, 149,150]. Table 1 summarizes some of the recent and uncommon fucoidans applications based on in-vitro or in-vivo studies, in addition to biogenic resources and physicochemical features.…”
Section: Recent Uncommon Applicationsmentioning
confidence: 99%
“…As alginic acid and its derivatives have good stability, solubility and viscosity and are safe, they are often used as excipients for food or pharmaceutical preparations to achieve thickening, stability and emulsification [ 13 ]. However, recent studies have shown that alginic acid and its derivatives also have good biocompatibility, antioxidant activity and anti-inflammatory activity [ 14 , 15 , 16 , 17 ]. At present, they are mostly commonly applied in cosmetics, and there are various anti-wrinkle, moisturizing and anti-ultraviolet products available [ 6 ].…”
Section: Alginic Acid and Its Derivativesmentioning
confidence: 99%
“…It is resistant to acid, but decarboxylation occurs when it is reacted with concentrated hydrochloric acid. It exhibits selective adsorption effects towards metal ions [ 16 ], in particular, Fe (Ⅱ) ions [ 18 , 19 ].…”
Section: Alginic Acid and Its Derivativesmentioning
confidence: 99%